Foreign Fighters, Rebel Command Structure, and Civilian Targeting in Civil War - Doctor, Austin C. (Terrorism and political violence, 2022)
Recent studies find that the presence of foreign fighters in a rebel organization may increase levels of anti-civilian violence in civil war. But why? Evidence from some cases indicates that foreign fighters may be used intentionally by local rebel commanders to carry out abusive operations against noncombatants. Other cases, however, suggest that foreign fighters possess greater capacity for independent agency in war, stepping outside the chain of command to inflict harm against local noncombatants. We argue that variation in a rebel group’s command structure—specifically, their degree of centralization—offers a point of leverage with which to adjudicate between the generalizability of these competing explanations. We investigate this issue with an analysis of sixty-nine rebel groups active between 1989 and 2015. We find that the effect of foreign fighters on civilian targeting is conditional: foreign fighters are associated with greater levels of anti-civilian violence only when active in groups with centralized command structures. This study contributes to the nascent literature on foreign fighters, offering insight into how these actors step into the command structures of rebel organizations. This study also demonstrates that the abuse of civilians in conflict can be explained effectively based on the characteristics of armed parties.